2000
DOI: 10.1177/000486580003300306
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Sexual Violence?

Abstract: T his article critically assesses the main social policy responses to preventing rape following much feminist struggle to make sexual violence a public matter of legitimate concern. It considers the preventative potential of legal measures, anti-violence campaigns waged by feminist and men's groups in the US and Australia, public education campaigns in Schools and Universities, and public awareness campaigns sponsored by the state.We argue that sexual violence is not amenable to quick fix strategies that place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 32 publications
1
60
0
1
Order By: Relevance
“…Governments, community groups and individuals often champion community education as a strategy to reduce sexual violence. In an earlier review of community education and education programmes in schools and universities, Kerry Carrington and I argued that many of these programmes adopted a 'quick-fix' workshop approach to rape prevention education (Carmody and Carrington, 2000). We were also critical of the reliance on psychological discourse, the limited evaluation of programmes, their inability to lead to lasting attitude change and the risk avoidance focus, especially for women.…”
Section: Reconceptualizing Violence Prevention Policies and Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Governments, community groups and individuals often champion community education as a strategy to reduce sexual violence. In an earlier review of community education and education programmes in schools and universities, Kerry Carrington and I argued that many of these programmes adopted a 'quick-fix' workshop approach to rape prevention education (Carmody and Carrington, 2000). We were also critical of the reliance on psychological discourse, the limited evaluation of programmes, their inability to lead to lasting attitude change and the risk avoidance focus, especially for women.…”
Section: Reconceptualizing Violence Prevention Policies and Strategiesmentioning
confidence: 99%
“…We were also critical of the reliance on psychological discourse, the limited evaluation of programmes, their inability to lead to lasting attitude change and the risk avoidance focus, especially for women. Parrot's (1990) review of 26 US university programmes was also cited, which revealed only two programmes aimed at changing men's behaviour and 21 for women (see Carmody and Carrington, 2000, for a detailed discussion). An alternative approach to prevention building on links between sexual ethics could look somewhat different.…”
Section: Reconceptualizing Violence Prevention Policies and Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However most of the evaluated programmes have been in either university or college settings in the United States. In 1999 Carmody and Carrington (2000) analysed 18 evaluations of rape education programmes. A further analysis was conducted of Australian anti-violence education funded by the Federal government (Carmody, 2001).…”
Section: Educating About Dangermentioning
confidence: 99%
“…Rather, disclosing past experiences of (male) violence continues to be caught up in discourses and femininity, where women are ultimately perceived as the 'poor girl' and the perpetrator the 'dangerous other' (Lamb 1999a, 108). As Carmody and Carrington (2000) argue, there are some apparent dangers in creating dichotomies based around 'innocent' women and 'evil' men when discussing instances of sexual violence. Significantly, the reliance on traditional gender discourses not only operates to simplify women's experiences of abuse, it also masks the wider social forces that contribute to the culture of violence (Carmody 2006;Marecek 1999).…”
mentioning
confidence: 99%